Effect of different torques on dentinal crack formation following canal preparation using neoniti rotary system - Akam Saeidi; Mahmood Reza Hamidi; Azadeh Harandi; Mina Habibolahpour; Hemmat Gholinia (Babol University of Medical Sciences, 2018)
Introduction: The aim of this study was to determine the incidence of dentinal cracks in the mesial root of maxillary molar during canal preparation using Neoniti system in different torque settings. Materials &Methods: In this in-vitro study, 60 maxillary molars extracted for various reasons were selected. The teeth were divided into 4 groups: one group(n=15) without preparation was considered as a control group (unprepared control group), the other 3 groups prepared with rotary neoniti system: group with standard torque (1.5 N/CM2)(n=15), group with high torque (2N/CM2)(n=15), and group with low torque (1N /CM2)(n=15). After a canal preparation procedure, the teeth were horizontally sectioned at 3, 6 and 9 mm from the apex. All sections were examined for determining the presence of cracks using a stereomicroscope. Data were analyzed using chi-square test. Results: There was no crack in the control group. The number of cracks was significantly higher in the high-torque group (80%) than standard- and low-torque groups (20%, 26.7%, respectively) (p<0.001). However, no significant difference was found between the standard-torque group and low-torque group (p<0.001). Conclusion: According to this study result, to avoid crack formation in higher torques using motors with torque control option is suggested.